2021
DOI: 10.1080/14756366.2021.1900162
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-TB properties, in silico target validation, molecular docking and dynamics studies of substituted 1,2,4-oxadiazole analogues against Mycobacterium tuberculosis

Abstract: The alarming increase in multi- and extensively drug-resistant (MDR and XDR) strains of Mycobacterium tuberculosis (MTB) has triggered the scientific community to search for novel, effective, and safer therapeutics. To this end, a series of 3,5-disubstituted-1,2,4-oxadiazole derivatives ( 3a–3i ) were tested against H37Rv, MDR and XDR strains of MTB. Of which, compound 3a with para-trifluorophenyl substituted oxadiazole showed excellent activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 113 publications
0
7
1
Order By: Relevance
“…Like in our study, the ligands showed comparable binding affinities with the standard drugs. In contrast to our study, the main stabilizing interactions between the compounds and the enzyme were π - π interactions with the aromatic amino acid residues Phe1590, Tyr1637, Phe1585, Tyr1674, Phe1670, and the catalytic His1699 with intermittent hydrogen bonding with Ser1636 and Asn1640 [ 38 ]. In another study, five new benzofuran derivatives were reported to have sufficient binding affinity for the pks-13 synthase with an alternative binding mode to the active site [ 42 ].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Like in our study, the ligands showed comparable binding affinities with the standard drugs. In contrast to our study, the main stabilizing interactions between the compounds and the enzyme were π - π interactions with the aromatic amino acid residues Phe1590, Tyr1637, Phe1585, Tyr1674, Phe1670, and the catalytic His1699 with intermittent hydrogen bonding with Ser1636 and Asn1640 [ 38 ]. In another study, five new benzofuran derivatives were reported to have sufficient binding affinity for the pks-13 synthase with an alternative binding mode to the active site [ 42 ].…”
Section: Discussioncontrasting
confidence: 79%
“…The interactions of the mycolic acids with other cell wall components make the mycobacterial cell walls very unique and contribute to the challenges associated with mycobacterium especially its pathogenesis, persistence, and chemotherapy. Given the critical role of mycolic acids in mycobacterium cell viability and pathogenesis, enzymes involved in mycolic acids biosynthesis, such as pks-13 present novel targets for drug development [ 38 ]. On the other hand, mycobacterial ATP synthase is another validated drug target and compounds inhibiting this enzyme are promising drug candidates [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected protein crystal structures were prepared, solvated and minimized, as previously described [ 64 , 65 , 66 ], in order to remove any potential artifacts caused by crystal packing. The binding sites were then determined, and all co-crystallized ligands were extracted and redocked into their appropriate binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…The value of the correlation coefficient ( r ) determines the strength of association between the two sets of variables. Generally, a value of | r | between 0.1–0.3 indicates a small association, 0.3–0.5 is medium, and 0.5–1.0 indicates a large association [ 66 ]. Furthermore, this enzyme showed another high correlation with LigScore1 ( r = −0.63).…”
Section: Resultsmentioning
confidence: 99%